Does Testosterone Influence Young Adult Romantic Partners' Accommodation During Conversations About Stressors?. (19th June 2020) - Dhillon, Anuraj; Denes, Amanda; Crowley, John P; Ponivas, Ambyre; Winkler, Kara L; Bennett, Margaret
Abstract: The present study contributes to a growing line of research exploring the associations between physiology and communication behavior. Specifically, this study investigated the influence of testosterone (T) on perceptions of partners' accommodative and nonaccommodative behaviors during a conversation about a relational stressor, and their subsequent association with satisfaction with the conversation. One hundred individuals participated in the study, which included a pre-survey, lab visit, and post-survey. Results revealed that for women, T was negatively associated with perceived partner accommodation and satisfaction with the conversation. Findings uncovered significant mediation effects of women's perceived partner (non)accommodation, while revealing several partner effects. Furthermore, the study found that satisfaction with the conversation was positively predicted by partner accommodation and negatively predicted by partner nonaccommodation for both women and men. These results indicate the utility of communication accommodation theory in examining conflict conversations and imply that T may influence communicative behaviors during conversation about a relational stressor.